La guerra civil española en los juegos y entornos lúdicos - Kuschel, Daniela (La Casa de la Riqueza. Estudios de la Cultura de España, 2023)
This book brings together different perspectives on the representation of the Spanish Civil War in digital and analog games, considering them an important part of the cultural production inspired by this historical event. Games must be understood as powerful disseminators of historical stories due to their influence on the processes of memory and reification of the past. Therefore, it is essential to analyze the ideologies they transmit and the visions of the past they offer to players-just like literature, cinema and comics. In this sense, this work introduces the study of games about the Civil War and evaluates the recreational environments in which they appear. It aims to reflect on how games, as distinctive media, can enrich research on conflict and historical memory in general. The case studies of games set in the Spanish Civil War allow us to discover and discuss the visions about the historical moment that circulate in the world of games. The Spanish Civil War in games and recreational environments also offers an overview of methods and theories for the analysis of games as cultural artifacts.